2015
DOI: 10.1186/s12916-015-0408-2
|View full text |Cite
|
Sign up to set email alerts
|

The public health impact of malaria vaccine RTS,S in malaria endemic Africa: country-specific predictions using 18 month follow-up Phase III data and simulation models

Abstract: BackgroundThe RTS,S/AS01 malaria vaccine candidate recently completed Phase III trials in 11 African sites. Recommendations for its deployment will partly depend on predictions of public health impact in endemic countries. Previous predictions of these used only limited information on underlying vaccine properties and have not considered country-specific contextual data.MethodsEach Phase III trial cohort was simulated explicitly using an ensemble of individual-based stochastic models, and many hypothetical vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 31 publications
6
40
0
Order By: Relevance
“…In addition, not explicitly accounting for the fate of severe malaria cases that do not make it to health facilities implies that national level burden of disease statistics for P. falciparum malaria, such as WMR, are also highly uncertain. Recently, several geography-specific predictions of malaria intervention impact and cost-effectiveness from OpenMalaria have allowed for national levels of effective treatment for uncomplicated disease [30, 31], but so far not for variations in access to in-patient care. It is not clear whether even these analyses accurately capture the quantitative impact of access to effective of treatment on subsequent burden, since the strength of this relationship is not well calibrated against field data, which is also lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, not explicitly accounting for the fate of severe malaria cases that do not make it to health facilities implies that national level burden of disease statistics for P. falciparum malaria, such as WMR, are also highly uncertain. Recently, several geography-specific predictions of malaria intervention impact and cost-effectiveness from OpenMalaria have allowed for national levels of effective treatment for uncomplicated disease [30, 31], but so far not for variations in access to in-patient care. It is not clear whether even these analyses accurately capture the quantitative impact of access to effective of treatment on subsequent burden, since the strength of this relationship is not well calibrated against field data, which is also lacking.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of massive amounts of geolocation data means that modeling of the likely impacts of specific intervention programs (like RTS,S vaccination) in specific places and times has become feasible (Penny et al 2015a), and these profuse data are available for calibration and validation of models. This sets a high bar for malaria modeling: Fitting complex models to multiple types of data is challenging, and model predictions are always likely to be unreliable at very high spatial resolution.…”
Section: Geographical Specificitymentioning
confidence: 99%
“…The circumsporozoite protein (CSP), a major sporozoite surface protein, has been identified as the antigen to which the antibody response is dominant humans and animals immunized with irradiated sporozoites (Nussenzweig and Nussenzweig, 1984;Zavala et al, 1986), making it a leading vaccine candidate (Herrington et al, 1990). The most advanced formulation (RTS,S) has now been extensively tested in Phase III trials, where it was shown to help diminish clinical cases, but not to prevent infection (Bejon et al, 2013;Penny et al, 2015;Stoute et al, 1997). It is likely that other, as yet unidentified antigens are implicated in the sterile immunity induced by irradiated sporozoites (Gruner et al, 2007;Kumar et al, 2006;Mauduit et al, 2010) (Chia et al, 2014;Longley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%